Organization Based Self Esteem dan Kepemimpinan Autentik sebagai Faktor Organizational Citizenship Behavior - Sevia Khusna; Bagus Wicaksono; Pratista Satwika (INSAN Jurnal Psikologi dan Kesehatan Mental, 2023)
Organizational citizenship behavior is an important issue in achieving effectiveness and efficiency within an organization. This study aims to determine the correlation between organization-based self-esteem and authentic leadership with employees' organizational citizenship behavior. This is a quantitative study with a sample of 382 civil servants from Boyolali, Indonesia, selected using a cluster random sampling technique. The instruments used are organizational citizenship behavior, organization-based self-esteem, and authentic leadership scale. Based on the results, there is a correlation between organization-based self-esteem and authentic leadership with organizational citizenship behavior. Organization-based self-esteem and authentic leadership are significantly correlated with organizational citizenship behavior (p < .05). This study found that authentic leadership and organization-based self-esteem are both capable of facilitating the emergence of organizational citizenship behavior in employees.